## Given: Q = 7m + 3n, R = 11 – 2m, S = n + 5, and T = -m – 3n + 8. Simplify [Q – R] + [S – T].

Question

Lost your password? Please enter your email address. You will receive a link and will create a new password via email.

Lorem ipsum dolor sit amet, consectetur adipiscing elit.Morbi adipiscing gravdio, sit amet suscipit risus ultrices eu.Fusce viverra neque at purus laoreet consequa.Vivamus vulputate posuere nisl quis consequat.

## Answers ( No )

Breaking each piece down

Q-R

(7m+3n) – (11- 2m)

7m + 3n -11- 2m

5m +3n – 11

S-T

(n+5)- (-m-3n)

n+5-m-3n

-2n +5 – m

(5m +3n -11) + (-2n +5 -m )

= 4m + n -6

Answer:Step-by-step explanation:Given :,,

, and

Now ,

[ ∵ (-)(+)=(-) and (-)(-)=(+)]

[Note : when -1 is outside the parenthesis it indicates that -1 should be multiplied with each of the terms present inside the parenthesis .]

[Combine like terms.]

[ ∵ (-)(+)=(-) and (-)(-)=(+)]

[Combine like terms.]

Now,

[combine like terms]

Hence,